Contact Tracing and COVID-19: The South Korean Context for Public Health Enforcement. Issue 4 (1st December 2020) - DiMoia, John P.
Abstract: Although South Korea's response to COVID-19 has received international praise, the nation's public health policy raises numerous privacy concerns, with a growing number of civil society groups joining the conversation. Following changes to public health law in 2015 in response to the MERS (Middle Eastern Respiratory Syndrome) crisis, South Korea's KCDC (Center for Disease Control) reconfigured its enforcement practice with measures tied to the movements of infected patients. New laws allow for the use of information communications technology and personal data (cell phone, CCTV, credit card transactions) to track patients, thereby identifying the possible routes of transmission for disease. Through mid-April 2020, this system received extensive praise, but more recently, with the "Itaewon Cluster, " centered in a popular nightclub district, citizens are starting to raise concerns. Itaewon is associated with prostitution due to its legacy of proximity to an American military base, and by extension, the presence of foreigners in general, including LGBT clubs. While contact tracing promises to preserve the anonymity of data, the significant rise in case numbers since May 2020 has resulted in calls for targeting these groups—foreigners, LGBT, English teachers—suggesting that xenophobia and social stigma continue to represent powerful forces.